Pollen diets and niche overlap of honey bees and native bees in protected areas - Elliott, Brittany; Wilson, Rachele; Shapcott, Alison; Keller, Alexander; Newis, Ryan; Cannizzaro, Chris; Burwell, Chris; Smith, Tobias; Leonhardt, Sara D.; Kämper, Wiebke; Wallace, Helen M. (Basic and applied ecology, 2021)
•Introduced honey bees dominated bee assemblages in protected Australian heathlands.•Metabarcoding revealed that honey bee pollen diets overlap with Tetragonula (stingless bees) and species of braUnsapis.•On average, honey bee individuals carried significantly more species of pollen than individuals of all other bee species.•Collectively, Australian native bees visited more plant species than introduced honey bees. The decline of both managed and wild bee populations has been extensively reported for over a decade now, with growing concerns amongst the scientific community. Also, evidence is growing that both managed and feral honey bees may exacerbate threats to wild bees. In Australia, there are over 1600 native bee species and introduced European honey bees (Apis mellifera) have established throughout most landscapes. There is a major gap in knowledge of the interactions between honey bees and native bees in Australian landscapes, especially floral resource use. Here we report on the pollen diets of wild bees in protected areas of coastal heathland, an ecosystem characterised by mass flowering in late winter and spring. We sampled bees within three sites and DNA metabarcoding was used to compare the pollen diets of honey bees and native bees. We recorded 2, 772 bees in total, with 13 genera and 18 described species identified. Apis mellifera was the most common species across all locations, accounting for 42% of all bees collected. Native bee genera included eusocial Tetragonula (stingless bees) (37%), and semi-social Exoneura and Braunsapis (19.8% combined). Metabarcoding data revealed both Tetragonula and honey bees have wide foraging patterns, and the bipartite network overall was highly generalised (H2’ = 0.24). Individual honey bees carried pollen of 7–29 plant species, and significantly more species than all other bees. We found niche overlap in the diets of honey bees and native bees generally (0.42), and strongest overlap with stingless bees (0.70) and species of Braunsapis (0.62). A surprising finding was that many species carried pollen from Restionaceae and Cyperaceae, families generally considered to be predominantly wind-pollinated in Australia. Our study showed introduced honey bee use of resources overlaps with that of native bees in protected heathlands, but there are clear differences in their diet preferences.